0;(x-2)(x+1)>0;" alt="x^2-x-2>0;(x-2)(x+1)>0;" align="absmiddle" class="latex-formula">
x є ![(-\infty;-1) \cup (2;+\infty) (-\infty;-1) \cup (2;+\infty)](https://tex.z-dn.net/?f=%28-%5Cinfty%3B-1%29+%5Ccup+%282%3B%2B%5Cinfty%29)
1;x^2-x-2<2^0;\\\\x^2-x-2-1<0;x^2-x-3<0;\\\\D=1+12=13;a=1>0;-1>x_1=\frac{1-\sqrt{13}}{2};\\\\x_2=\frac{1+\sqrt{13}}{2}>2;" alt="2>1;x^2-x-2<2^0;\\\\x^2-x-2-1<0;x^2-x-3<0;\\\\D=1+12=13;a=1>0;-1>x_1=\frac{1-\sqrt{13}}{2};\\\\x_2=\frac{1+\sqrt{13}}{2}>2;" align="absmiddle" class="latex-formula">
x є ![(\frac{1-\sqrt{13}}{2};(\frac{1+\sqrt{13}}{2}) (\frac{1-\sqrt{13}}{2};(\frac{1+\sqrt{13}}{2})](https://tex.z-dn.net/?f=%28%5Cfrac%7B1-%5Csqrt%7B13%7D%7D%7B2%7D%3B%28%5Cfrac%7B1%2B%5Csqrt%7B13%7D%7D%7B2%7D%29)
обьединяя окончательно ![(\frac{1-\sqrt{13}}{2};-1) \cup(2;\frac{1+\sqrt{13}}{2}) (\frac{1-\sqrt{13}}{2};-1) \cup(2;\frac{1+\sqrt{13}}{2})](https://tex.z-dn.net/?f=%28%5Cfrac%7B1-%5Csqrt%7B13%7D%7D%7B2%7D%3B-1%29+%5Ccup%282%3B%5Cfrac%7B1%2B%5Csqrt%7B13%7D%7D%7B2%7D%29)